Determining the Impact of Clinical Pharmacist-Provided Patient Education on Quality of Life (QOL) Outcome in Type II Diabetes Mellitus in Rural Population - Ramanath , K. V.; Santhosh , Y. L. (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Background: Diabetes mellitus is one of the significant causes of causing complicated issues /disabilities across the world. Hence proper education to maintain the glycemic level is typically very essential. Patient knowledge, attitude, and the practice of diabetes is an important aspect, and it directly affects the Quality of life. Objective: The study's main aim is to assess the impact of clinical pharmacist-provided patient education on Quality of life outcomes. Methodology: A prospective randomized control study was conducted in the general medicine department of a tertiary care hospital. Patients were enrolled and randomized into control and intervention groups based on inclusion and exclusion criteria. A total of three follow-ups were done from the baseline. At each follow-up, both groups administered questionnaires and measured their blood glucose. Next, give a Patient information leaflet (PIL) and formal counseling to the intervention group at each level and the control group at the final follow-up. Results and Discussion: A total of one hundred and thirteen patients were enrolled. A significant increase in QOL, KAP, and adherence scores (P value< 0.05) was observed in the intervention group compared to the control group. A Blood glucose level in the intervention group was significantly changed but was altered in the control group. Conclusion: Hence this study concludes that pharmacist plays a vital role in educating patients to maintain their Quality of life.